PENGARUH STRUKTUR KEPEMILIKAN, AUDIT FEE DAN AUDIT REPORT LAG TERHADAP INTEGRITAS LAPORAN KEUANGAN - Louw, Febriana; Indah, Nopiani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to investigate the impact of ownership structure, audit fees, and audit report lag on the integrity of financial statements. This research is of an associative nature employing a quantitative approach. The research sample consists of companies in the industrial sector listed on the Indonesia Stock Exchange during the period 2017-2021. Using purposive sampling method, 10 companies were selected as the research sample. The data analysis technique employed in this research is multiple linear regression analysis assisted by Statistical Product and Service Solution (SPSS) version 25. The research findings indicate that ownership structure has a negative impact on the integrity of financial statements, audit fees do not have an impact on the integrity of financial statements, while audit report lag has a positive impact on the integrity of financial statements in companies in the industrial sector listed on the Indonesia Stock Exchange